Area-based socioeconomic conditions and urban malaria and diarrhea mortalities in Accra, Ghana. - Fobil, J.N.; Loag, W.; Schwarz, N.; Rodrigues, F.; Meyer, C.G.; Kraemer, A.; May, J. (My University, 2012)
Health inequalities are linked to inequalities in Socioeconomic Status (SES). While infant malaria/diarrhea mortality is widely studied, not very much is known about the influence of area-based measures of SES and all age urban malaria and diarrhea mortalities. To assess the relationship between area-based SES and malaria/diarrhea mortalities and whether these differed across SE-classes in an urban area in a low income country. Proportional mortality rates, computed from 24716 reported death records, collected from Accra over the period 1998-2002 were compared with area-based socioeconomic data in multivariate linear regression analyses in an ecological study design. While malaria mortality showed strong evidence of significant differences across the SE-quintiles (Mean PMRfd = 0.030; 95% CI = 0.010 0.049 p = 0.0008), no such differences in diarrhea mortality were observed (Mean PMRfd = 0.027; 95% CI = 0.014 0.040; p = 0.288). Analyses showed weaker associations between area-based SE-conditions and diarrhea mortality than that observed for malaria mortality. We conclude that all age urban malaria mortalities were more sensitive to changing area-based SE-conditions than diarrhea mortalities suggesting perhaps that social interventions were more effective in diarrhea control compared to malaria.